Alcohol, Substance Use and Psychosocial Competence of Adolescents in Selected Secondary Schools in Uganda: A Cross Sectional Survey - Abbo, Catherine; Okello, Elialilia S.; Muhwezi, Wilson; Akello, Grace; Ovuga, Emilio; Makinodan, Manabu (International neuropsychiatric disease journal, 2016)
To determine the nature and extent of alcohol and substance use and 2) To describe the relationship between alcohol use and psychosocial competence among secondary school youths in Northern and Central Uganda. Study Design—This was a cross-sectional study. Place and Duration of study—Departments of Mental Health, Gulu University (Northern Uganda) and Department of Psychiatry, Makerere University College of Health Sciences (Central Uganda) between September 2011 and April 2012. Methodology—Four (4) and eight (8) secondary schools located in the rural and urban areas of Gulu and Kampala districts respectively were randomly selected to participate in the survey. A total of 3,200 students aged 12 to 24 years were recruited by proportionate multistage sampling. Data was collected using a socio-demographic questionnaire that included questions about nature and frequency of alcohol and substance use. A pre-tested self-administered survey questionnaire with scales to measure components of psychosocial competence (PSC) was administered. Data was entered in Epidata, and exported to SPSS version 16.0 for analysis. Psychosocial competence was classified as high or low depending on the responses in the sub-scales of decision making, self efficacy, empathy, emotional awareness, coping with stress and emotions, and accurate self-assessment and self-confidence. Results—A total of 2,902 questionnaires comprising of 2,502, (86.2%) from Kampala district and 400 (13.8%)) from Gulu district were analyzed. Male to female ratio was 1:1 with an age range of 12 to 24 years and a mean of 16.5. About 70.1% had ever used alcohol and substances. Only 39.1% used substances regularly. The commonest substance used was alcohol (23.3%), followed by kuber (10.8%), khat (10.5%), aviation fuel (10.1%), cannabis (9.2%) and cigarettes (5.9%). Respondents from the Gulu district were twice more likely to use all substances. Users and regular users from the North Northern Uganda had lower psychosocial competence. Factors significantly associated with non-use of alcohol were high levels of self-confidence, non-use of cannabis and kuber and age. In the alcohol user groups, a high level of coping was associated with discontinued and experimental use of drugs of abuse. Conclusion—More than two-thirds (70.1%) of young people in this study had ever used substances of abuse only once and slightly over a third had used it regularly. From the perspectives of service provision, mental health promotion and prevention of illicit substance use, school mental health programmes that target both non-users and users are recommended.
Keywords: Substance use; Young people; Psychosocial competence; Uganda